Setting research priorities to reduce global mortality from preterm birth and low birth - Rajiv Bahl Department of Child and Adolescent Health and Development, World Health Organization, Geneva, Switzerland; Jose Martines; Nita Bhandari; Zrinka Biloglav; Karen Edmond; Sharad Iyengar; Michael Kramer; Joy E. Lawn; D. S. Manandhar; Rintaro Mori; Kathleen M. Rasmussen; H. P. S. Sachdev; et al. (Edinburgh University Global Health Society, 2012)
This paper aims to identify health research priorities that could improve the rate of progress in reducing global neonatal mortality from preterm birth and low birth weight (PB/LBW), as set out in the UN's Millennium Development Goal 4.